Time requirements and health effects of participation in colorectal cancer screening with colonoscopy or computed tomography colonography in a randomized controlled trial - van Dam, L.; de Wijkerslooth, T. R.; de Haan, M. C.; Stoop, E. M.; Bossuyt, P. M. M.; Fockens, P.; Thomeer, M.; Kuipers, E. J.; van Leerdam, M. E.; van Ballegooijen, M.; Stoker, J.; Dekker, E.; Steyerberg, E. W. (Endoscopy, 2013)
Background and study aims: Time limitations and unwanted health effects may act as barriers to participation in colorectal cancer (CRC) screening. The aim of the study was to measure the time requirements and health effects of colonoscopy and computed tomography colonography (CTC) screening.Patients and methods: This was a prospective diary study in a consecutive sample within a randomized controlled CRC screening trial, comparing primary colonoscopy and CTC screening for average-risk individuals aged 50 – 74 years. The diary ended when all screening-related complaints had passed.Results: The diary was returned by 75 % (241/322) of colonoscopy and 75 % (127/170) of CTC screenees. The median interval between leaving home and returning from the examination was longer for colonoscopy (4 hours and 18 minutes [4:18], interquartile range [IQR] 3:30 – 5:00) than for CTC (2:30 hours, IQR 2:06 – 3:00; P < 0.001). Similarly, the time to return to routine activities was longer after colonoscopy (3:54 hours, IQR 1:48 – 15:00) than after CTC (1:36 hours, IQR 0:54 – 4:42). The duration of screening-related symptoms after the examination was shorter for colonoscopy (11:00 hours, IQR 2:54 – 20:00) than for CTC (22:00 hours; IQR 5:30 – 47:00; P < 0.001). Abdominal complaints were reported more frequently after CTC. Anxiety, pain, and quality of life worsened during the screening process, with no differences between the two examinations.Conclusions: Compared with colonoscopy, CTC screening required less time and allowed screenees to return to their daily activities more quickly. In contrast, CTC was associated with a twofold longer duration of screening-related symptoms. Feelings of anxiety, pain, and quality of life scores were similar during colonoscopy and CTC screening. These results should be incorporated into cost-effectiveness analyses of CRC screening techniques.